The replicative helicase MCM recruits cohesin acetyltransferase ESCO2 to mediate centromeric sister chromatid cohesion. (21st June 2018) - Ivanov, Miroslav P; Ladurner, Rene; Poser, Ina; Beveridge, Rebecca; Rampler, Evelyn; Hudecz, Otto; Novatchkova, Maria; Hériché, Jean‐Karim; Wutz, Gordana; van der Lelij, Petra; Kreidl, Emanuel; Hutchins, James RA; et al.
Abstract: Chromosome segregation depends on sister chromatid cohesion which is established by cohesin during DNA replication. Cohesive cohesin complexes become acetylated to prevent their precocious release by WAPL before cells have reached mitosis. To obtain insight into how DNA replication, cohesion establishment and cohesin acetylation are coordinated, we analysed the interaction partners of 55 human proteins implicated in these processes by mass spectrometry. This proteomic screen revealed that on chromatin the cohesin acetyltransferase ESCO2 associates with the MCM2‐7 subcomplex of the replicative Cdc45‐MCM‐GINS helicase. The analysis of ESCO2 mutants defective in MCM binding indicates that these interactions are required for proper recruitment of ESCO2 to chromatin, cohesin acetylation during DNA replication, and centromeric cohesion. We propose that MCM binding enables ESCO2 to travel with replisomes to acetylate cohesive cohesin complexes in the vicinity of replication forks so that these complexes can be protected from precocious release by WAPL. Our results also indicate that ESCO1 and ESCO2 have distinct functions in maintaining cohesion between chromosome arms and centromeres, respectively. Synopsis: Binding of the DNA replication helicase MCM to ESCO2 enables the acetyltransferase to acetylate cohesin complexes on nascent DNA. This modification protects cohesin from precocious release by WAPL and is required for maintenance of sister chromatid cohesion at centromeres. ESCO2 is recruited to chromatin by MCM. ESCO2‐MCM interactions are important for cohesin acetylation on nascent chromatin and centromeric cohesion. ESCO1 and ESCO2 maintain cohesion between chromosome arms and centromeres, respectively. Abstract : Recruitment of cohesin acetyltransferase ESCO2 by the MCM2‐7 replication complex to chromatin is required for cohesin acetylation around replication forks to maintain centromeric cohesion.